Produksi Syngas melalui Crossdraft Gasifier ditinjau dari Variasi Temperatur dan Massa Jerami Padi sebagai Filter - Ahmad Gilang Abdillah Yama; Muhammad Rafiq Vitruvi; Ayu Andira; Arizal Aswan; Yohandri Bow; Ida Febriana; Adi Syakdani; Rusdianasari Rusdianasari (Jurnal Teknologi, 2022)
Utilizing alternative energy is one strategy for resolving the petroleum energy dilemma. There are a number of ways to use coal as an alternative energy source, including the gasification process. In the presence of less oxygen than necessary for stoichiometric combustion, solid fuels are thermochemically converted into combustible fuels during the gasification process. The temperature and mass changes of rice straw used as a syngas filter were examined in this work in order to create a crossdraft gasifier prototype. Cleaning systems are directly incorporated into gasifiers to create them. In order to produce syngas of excellent quality, this study set out to establish the ideal temperature and rice straw filter mass. It also sought to identify the maximum LHV value for changes in rice straw filter mass. According to the study's findings, a temperature of 650 °C was needed to achieve a decent thermal efficiency of 16.56%, and a mass of 500 g of rice straw served as the ideal filter mass for syngas with a quality composition of 9.8% CO, 6.32% H2, and 1.97% CH4. The mass of 500 grams of rice straw with the greatest LHV value was 14,529.4 Kj/Kg.